Deception, Pain, and Placebo: Applying the Brummett‐Salter Deception Framework. Issue 1 (24th February 2023) - Wasserman, Jason Adam
Abstract: In this commentary, I explore the usefulness of the framework Abram Brummett and Erica K. Salter present in their article "Mapping the Moral Terrain of Clinical Deception." Deception cases are divisive because they nearly always evoke the metadilemma of clinical ethics: a clash between duties (in these cases, truth telling) and consequences (whatever good might come of the lie). Here, I describe a patient case in which the clinical team considered deceiving a patient about his pain‐medicine dosage in exchange for his allowing the clinicians to properly care for his percutaneous endoscopic gastrostomy tube stoma, so as to prevent infection. Applying the framework that Brummett and Salter have developed helped our clinical team parse the numerous complex issues involved. The nuances of our case also illustrated additional ways in which the ethics of deception needs to be further refined .